Situation and problems in the supply chains of traditional cheeses in Croatia - Željka Mesić; Marija Cerjak; Damir Kovačić (Mljekarstvo)
Croatian producers of traditional cheeses often do not have the financial and/or organizational ability to act independently on the market, Thusit is important to get involved in supply chains in order to improve the competitiveness of their products. The main objective of this study was to determine the status and the problems related to the supply chains of traditional cheeses in Croatia. The survey was conducted on 36 chain members (including 12 milk suppliers, 12 cheese producers and 12 customers). In the first stage of the study cheese producers were selected for interviews. During the interviews, each cheese producer was asked to identify the most important suppliers and customers, which were subsequently forwarded the questionnaire depending on their role in the supply chain. According tothe obtained results the key problems in supply chains of traditional cheeseswere the imbalance in bargaining power within the chain, especially between producers and customers, the high logistics’ costs, the lack of transparency in contractual relations, low rates of charge realisation, and the poor communication and information sharing among supply chain members. Results of this study might be used as theoretical basis to all respondents whose companies participated in the survey and could encourage them to improve the performance of their supply chains based on the identified problems.